Emerging Human Babesiosis with “Ground Zero” in North America - Yi Yang; Jevan Christie; Liza Köster; Aifang Du; Chaoqun Yao (Microorganisms, 2021)
The first case of human babesiosis was reported in the literature in 1957. The clinical disease has sporadically occurred as rare case reports in North America and Europe in the subsequent decades. Since the new millennium, especially in the last decade, many more cases have apparently appeared not only in these regions but also in Asia, South America, and Africa. More than 20,000 cases of human babesiosis have been reported in North America alone. In several cross-sectional surveys, exposure to Babesia spp. has been demonstrated within urban and rural human populations with clinical babesiosis reported in both immunocompromised and immunocompetent humans. This review serves to highlight the widespread distribution of these tick-borne pathogens in humans, their tick vectors in readily accessible environments such as parks and recreational areas, and their phylogenetic relationships.